Women's leadership development : caring environments and paths to transformation - Debebe, Gelaye, 1966- (Routledge studies in leadership research., 2019)
Readers come to the topic of leadership development with multiple interests--intellectual, professional, and personal--and with curiosity about how to apply concepts and tools to themselves and to support others. Women's Leadership Development: Caring Environments and Paths to Transformation addresses these concerns. The book offers an interdisciplinary framework of leadership effectiveness and brings this framework to life with detailed and illuminating descriptions of four leadership transformations facilitated by care-practices used in a specific leader development program. The book will be of interest to academics who teach leadership or conduct leadership research, HR professionals who are seeking fresh ideas for how to maximize the impact of leadership training for women, and anyone with a passion for personal growth and development.